2017
DOI: 10.1111/ecoj.12414
|View full text |Cite
|
Sign up to set email alerts
|

Locus of Control and its Intergenerational Implications for Early Childhood Skill Formation

Abstract: We propose a model in which parents have a subjective belief about the impact of their investment on the early skill formation of their children. This subjective belief is determined in part by locus of control (LOC), i.e., the extent to which individuals believe that their actions can influence future outcomes. Using a unique British cohort survey, we show that maternal LOC measured during the 1st-trimester strongly predicts early and late child cognitive and noncognitive outcomes. Further, we utilize the var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 90 publications
0
28
0
Order By: Relevance
“…Previous research has shown that individuals with positive control beliefs invest more in their own education (Coleman and Deleire 2003;Hadsell 2010) and in the education of their children (Lekfuangfu et al 2014), and adolescents' control beliefs are associated with parental socioeconomic status (Schurer 2015;Anger and Schnitzlein 2015). Lundborg et al (2015) show evidence on the education-related heterogeneity in the response to health shocks using Swedish administrative data, although the authors do not discuss the mechanisms.…”
Section: Mechanismmentioning
confidence: 97%
“…Previous research has shown that individuals with positive control beliefs invest more in their own education (Coleman and Deleire 2003;Hadsell 2010) and in the education of their children (Lekfuangfu et al 2014), and adolescents' control beliefs are associated with parental socioeconomic status (Schurer 2015;Anger and Schnitzlein 2015). Lundborg et al (2015) show evidence on the education-related heterogeneity in the response to health shocks using Swedish administrative data, although the authors do not discuss the mechanisms.…”
Section: Mechanismmentioning
confidence: 97%
“…A related non-cognitive skill is individual's perceived locus of control. This concept has received much attention from economists in recent years (Lekfuangfu et al, 2018, Abay et al, 2017, Cobb-Clark et al, 2016, Caliendo et al, 2015, Coleman and DeLeire, 2003. Individuals differ in their belief of how much control they have over important live outcomes.…”
Section: Non-cognitive Skillsmentioning
confidence: 99%
“…Moreover, there are critical periods for the development of human capabilitieswhich vary across skills -making it important to consider not only which interventions work, but also for whom and at which ages. Importantly, evidence is emerging that many non-cognitive skills like locus of control are correlated across generations (e.g., Anger 2012) and that a mother's locus of control is linked to a vast array of child outcomes (e.g., Lekfuangfu et al 2014). Thus, there is potential for interventions targeting locus of control to have important inter-generational consequences.…”
Section: Policy To Improve Locus Of Controlmentioning
confidence: 99%